Warisan Dan Keadilan: Membongkar Mitos Kesetaraan Harta Dalam Perspektif Hukum Islam - Ritonga, Raja; Siregar, Ilham Ramadan; Hamid, Asrul; Muda Nst, Andri; Hsb, Zuhdi (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2025)
This article aims to delve into the complexities of inheritance distribution and the challenges of wealth equality by detailing the perspectives of Islamic law. It seeks to unravel debates surrounding the myth of equality in inheritance distribution, underscoring the need for a deeper understanding within the framework of Islamic jurisprudence. Disparities in inheritance practices within Muslim communities often lead to internal family conflicts. Therefore, this article presents a critical perspective on inheritance practices that may not always be equitable, while proposing alternatives aligned with Islamic values. The research takes a qualitative form, utilizing library research methodology. Data is collected through the exploration of various articles and relevant scholarly works. Subsequently, findings are analyzed descriptively, encompassing an examination of Islamic legal literature on inheritance and practical case studies within Muslim communities. The results reflect the complexity of equality issues in the context of inheritance, offering a new understanding of implementing Islamic legal principles to achieve a more equitable distribution of wealth in line with Sharia objectives.